Affirmation of the Social Approach in the Case of Relocation of Community in Ciliwung Riverbank - Maring, Prudensius; Prakosawati, Elisabeth Endang (Komunitas, 2019)
Urban development projects often lead to social contraction between the technical-physical approach and the socio-cultural approach. To explain the problem, this paper inspires the concepts of urban anthropology and socio-cultural development. The study was conducted in 2016-2017 in community located in Ciliwung riverbank, Jakarta. The methods used include in-depth interviews, participatory observations, and document analysis. The results of the study show that although river normalization projects and relocation projects have been equipped with a policy framework and technical framework that accommodates the interests of the community, the implementation of the social approach has not been implemented consistently. This condition raises doubts, rejections, and resistance from the community to maintain the social, economic and environmental resources that have been ruled on the riverbanks. This research confirms the importance of affirming socio-cultural approaches in urban development programs and projects that are carried out consistently by fulfilling the prerequisites for freedom in time, financing, and management resources.